Status prawny Służby Parku Narodowego - Karpiuk, Mirosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Preservation, sustainable use and the restoration of resources, natural monuments and the elements of nature are one of the components creating the sphere of ecological security seen from the perspective of nature preservation. Within this system, there should be distinguished nature preservation services which are entrusted competences and tasks in that field. The National Park Service performs nature preservation tasks in national parks. Those entrusted with tasks in the institution of the National Park Service do not perform them on the basis of the service relationship (legal-administrative relation), but on the basis of employment relationship, as they are workers employed on various positions in this structure. Personnel perform activities related to nature preservation, scientific research and educational activities, as well as connected with the protection of the national park property, or preventing crimes and offences in the field of nature preservation.